A study of entrepreneurial potential and entrepreneurial personality traits among vocational colleges students in Malaysia: moderating effects of entrepreneurial mentoring / Norffadhillah Rofa - Rofa, Norffadhillah (2022)
The National Entrepreneurship Policy 2030 aims to unleash the potential of an entrepreneurial ecosystem. With initiatives, the government facilitates students and recent graduates in addressing student entrepreneurship. Thus, entrepreneurship-focused Technical Vocational Education and Training (TVET) is a part of the policy which has included Vocational Colleges (VC). It produces hands-on students to meet industry needs. Nevertheless, TVET graduates face discrimination in salary, competency, and working conditions. They discovered a supply-demand imbalance. Thus, it is necessary to study the traits that predict Entrepreneurial Potential (EP). This study also seeks to establish the link between Entrepreneurial Personality Traits (EPT) and Entrepreneurial Potential (EP) and the role of Entrepreneurial Mentoring (EM). It is because EPT of students involved in entrepreneurship education have developed EP. Data were collected by using systematic sampling. 500 questionnaires were given to students at VCs across Malaysia. Only 252 of 270 questionnaires were returned. The data were analyzed by using SPSS and PLS-SEM. This study seeks to understand the effects of EPT towards EP among VC students. The study found EPT are the best predictors of future success. A positive EPT affects EP, as well as EM has been shown to influence student`s potential. Students EP increased when they were EM by the lecturers. While, for the moderating effect, the findings revealed that EM has medium effect between EPT and EP. Possibly the increase of EM may reduce the effects on EPT and EP students and vice versa. Thus, this study would assist responsible authorities to provide lecturers with EM methods and develop entrepreneurship programs and activities for students. Furthermore, it supports VC’s desire to become more practical entrepreneurial hubs to boost students EP through their EPT. The psychosocial support and counselling also could help lecturers and students to encourage well- functioned of EM.